More than a Great Idea: Findings from the Profiles in Public Health Social Work Study. Issue 5 (1st June 2020) - Ruth, Betty J.; Marshall, Jamie Wyatt; Wachman, Madi; Marbach, Alexis; Choudhury, Nandini S.
ABSTRACT: Progress in refining the definition and basic concepts of public health social work (PHSW) is central to its revitalization. Advancing PHSW further depends on understanding the roles, domains, and daily activities of current PHSW practitioners in the contemporary workforce. The goal of the Profiles in PHSW Study is to explore how public health social workers conceptualize and locate their work. Using snowball sampling, 48 PHSW subjects with four or more years of professional experience were recruited; 34 (70.8%) participated. Qualitative survey responses were compiled and thematically analyzed; six themes emerged related to the nuances of integrating public health and social work, wide-ranging practice across systems and settings, leadership, visibility and viability, and recommendations for how to move PHSW forward. Findings suggest that intentional profession-wide integration of public health approaches into social work education, research, and practice is needed to strengthen the field's impact and role in advancing population health.